2018
DOI: 10.3390/healthcare6020043
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adult Day Services in Supporting the Occupational Participation of People with Dementia and Their Carers: An Integrative Review

Abstract: The increasing numbers of people with dementia places considerable stress on health and aged care services and has resulted in the development of community adult day services. Aim: The aim of this integrative review is to determine the extent to which these services support the occupational participation of people with dementia, and how they impact their primary carers. Method: The mixed-methods appraisal tool (MMAT) was used to identify relevant studies in the period 2011–2016. Results: Nine databases were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 44 publications
0
40
0
1
Order By: Relevance
“…In a review, attending adult day care was found to increase social engagement for people with dementia through participation in activities with peers with whom they feel safe and comfortable. Further, participants who attended adult day care exhibited significantly less depression and fewer behavioural issues compared to participants who did not attend (Du Preez, Millsteed, Marquis, & Richmond, 2018).…”
Section: Implications For Post-diagnostic Support To Reduce Unmet Needsmentioning
confidence: 90%
“…In a review, attending adult day care was found to increase social engagement for people with dementia through participation in activities with peers with whom they feel safe and comfortable. Further, participants who attended adult day care exhibited significantly less depression and fewer behavioural issues compared to participants who did not attend (Du Preez, Millsteed, Marquis, & Richmond, 2018).…”
Section: Implications For Post-diagnostic Support To Reduce Unmet Needsmentioning
confidence: 90%
“…2). Most eligible reviews addressed older adults and/or those with dementia and evaluated caregiver support (n = 10), [20][21][22][23][24][25][26][27][28][29] respite care and adult day programs (n = 9), [30][31][32][33][34][35][36][37][38] case management (n = 8), [39][40][41][42][43][44][45][46] or preventive home visits (n = 6) [47][48][49][50][51][52] (see Text Box 1 for descriptions of main intervention categories). The remaining reviews [53][54][55][56][57][58][59][60][61][62][63][64][65][66] were either very broad in scope (e.g., all nonpharmacologic interventions for dementia) or 1-2 reviews addressing an intervention (e.g., home-based primary care).…”
Section: Overview Of Eligible and Prioritized Systematic Reviewsmentioning
confidence: 99%
“…As such, the service will serve more as a transitional period to residential care than as a respite to postpone the need for NH admission [ 18 ]. As stated in a recent review by Du Preez et al (2018), intervention early in the caregiving process can offset caregiver stress through utilisation of adult day service support, respite and education [ 45 ]. Qualitative research, conducted as part of the current project, adds important information about the experience of day care from the perspective of family caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…A review by Du Preez et al highlighted that family caregivers often have limited contact with the day care services, and this lack of contact coupled with the inability of the day care services to offer person-centred activities contribute to non-utilisation of the services. However, when day care services actively invite caregivers to collaborate in the day care programme and provide caregiver education, counselling and support, institutionalisation is delayed [ 45 ]. Interviews with caregivers in the current project demonstrated the need for more flexibility in the number of opening days and opening hours.…”
Section: Discussionmentioning
confidence: 99%